Modeling and Simulation of Swarm Intelligence Algorithms for Parameters Tuning Of PID Controller in Industrial Couple Tank System - Mohd Khairuddin, Ismail; Ahmad Dahalan, Amira Sarayati; Zainal Abidin, Amar Faiz; Yee, Yang Lai; Nordin, Nur Anis; Siti Fatimah, Sulaiman; Jaafar, Hazriq Izzuan; Mohamad, Syahrul Hisham; Amer, Noor Hafizah (scientific.net, 2014)
Industrial tank system is widely used in consumer liquid processing and chemical processing industry. In liquid-based product manufacturing system, one of the main components consists of an industrial tank. This paper explores the applications of two swarm intelligence algorithms in optimizing the PID controller parameters. These swarm intelligence algorithms are Particle Swarm Optimization (PSO) and Firefly Algorithm (FA). Each agent of the swarm intelligence will represent a possible solution of the problem where each dimension corresponds to the PID controller’s parameters. Result obtained shows that there are potential in improving these algorithms to replace the conventional way of obtaining PID controller’s parameters.